TOWARDS EXCELLENCE IN THYROID SERVICE: AN ACCREDITED THYROID HOSPITAL - Chatchomchuan, Waralee; Thewjitcharoen, Yotsapon; Wanothayaroj, Ekgaluck; Krifliyawong, Sirinate; Rajatanavin, Rajata (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES We described our experience at Theptarin, the first hospital in Thailand to achieve an accreditation in thyroid service from Thailand Healthcare Accreditation Institute in 2021. METHODOLOGY Our infrastructure fit the criteria of specific disease accreditation. The important components were availability of thyroidologists and multidisciplinary specialists in related fields, a large volume of patients with long-term follow-up, supporting facilities which include surgery and radioactive iodine ablation. Key Performance Indexes (KPI) and evidence-based Clinical Practice Guidelines (CPG) for 3 common thyroid disorders (Graves’ disease, thyroid nodule, and differentiated thyroid cancer) were created. Patient service was redesigned to be patient-centered and lean. Educational activities were organized for both healthcare professionals and the public. Patients’ satisfaction was assessed. Research activities were also committed. RESULTS KPIs were set for 16 indicators. The consensus was reached for 7 CPG’s. There were 12,150 visits by patients with thyroid disorders in 2021. The follow-up rate increased from 88.6% in 2019 to 98.5% in 2021. The rate of ultrasono- graphy increased in patients with thyroid nodules (94.4% in 2019 to 98.5% in 2021). In patients with thyroid cancer, neither permanent hypoparathyroidism nor permanent recurrent laryngeal nerve injury occurred after surgery. Patients reported 86.9% satisfaction in 2021. Posters were displayed on world thyroid day and a multidisciplinary thyroid conference was organized. Eight researches in thyroid disorders were published in 2020-2021. CONCLUSION Accreditation for thyroid service is a testimony of excellence in patient care. It also serves as a model and set the stage for continuous improvement in outcome and safety of patient care.